Effect of Online Training of Emotion Regulation in Terms of Locus of Control on Medical Students’ Anger Control and Impulsiveness: A Quasi-Experimental Study - Yousef Khonya; Mohammad Narimani; Seyfullah Aghajani; Nader Hajloo (Taṣvīr-i salāmat, 2022)
Background. Lack of anger control and impulsiveness can lead to different personal and social harms. This study aimed to investigate the effect of emotion regulation training according to the source of control on anger control and impulsiveness of medical students. Methods. This quasi-experimental research was conducted with pre-test post-test design, including a control group with follow-up. The population consisted of general medicine students studying basic sciences and physiopathology. After completing three questionnaires of anger control, impulsivity, and locus of control, 60 students were randomly selected and assigned to experimental and control groups. The participants in the experimental group received eight sessions of emotion regulation training. The questionnaires were administered to all participants after training in two sessions of post-test and follow-up post-test. The data were analyzed using multivariate analysis of variance (MANOVA). The data were analyzed through two-factorial multivariate analysis of covariance (MANCOVA) using the Statistical Package for the Social Sciences (SPSS) v. 24. Results. Emotion regulation training and its interaction with the locus of control had a positive effect on anger and impulsiveness control. Conclusion. Training emotion regulation and other social skills to university students can help them face the challenges during their studies.